Consensual and conflictual democratization - Matteo Cervellati; Piergiuseppe Fortunato; Uwe Sunde (Institute for the Study of Labor (IZA), 2006)
We study the process of endogenous democratization from inefficient oligarchic systems in an economy where heterogeneous individuals can get involved in predation activities. The features of democracies are shown to be crucially related to the conditions under which democratization initially takes place. The political regime and the extent of redistribution implemented under it depend on the allocation of de facto political power across the different social groups. The cost of public enforcement of property rights depends on the extent of predation activities in the economy. The theory highlights the importance of inequality in natural resources and availability of human capital for endogenous democratic transitions. Multiple politico-economic equilibria can be sustained conditional on expectations about property rights enforcement. This generates history dependence. Democratic transitions supported by a large consensus serve as coordination device and lead to better protection of property and more stable political systems than democratic transitions imposed in conflictual environments. We test the novel predictions using available cross-country data. The link between the type of democratic transition and the outcomes under democracy is also investigated using novel data on constitutional principles. The findings support the theoretical predictions.
Keywords: H10; O20; N10; 330; democratization; oligarchy; conflict; consensual democracy; inequality; commitment; constitutional principles